2019
DOI: 10.1016/j.meddos.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric comparison of TomoDirect, helical tomotherapy, VMAT, and ff-IMRT for upper thoracic esophageal carcinoma

Abstract: All techniques are able to provide a homogeneous and highly conformal dose distribution. The TD technique is a good option for treating upper thoracic EC involvement. It could achieve optimal low dose to the lungs and spinal cord with acceptable PTV coverage. HT is a good option as it could achieve quality dose conformality and uniformity, while TD generated superior conformality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Sun et al [27] reported the dosimetric comparisons of 12 newly histologically diagnosed intracranial medulloblastoma patients using HT, VMAT, and IMRT and found that HT showed superior dose conformity as compared with IMRT and VMAT in PTVs. As discussed by Zhang et al [28], the CI for PTV 59.4 was similar among the 4 techniques (TomoDirect, HT, VMAT, and fixed-field intensity-modulated radiotherapy), and the CI for PTV 50.4 showed a statistical significance of HT.…”
Section: Biomed Research Internationalmentioning
confidence: 52%
“…Sun et al [27] reported the dosimetric comparisons of 12 newly histologically diagnosed intracranial medulloblastoma patients using HT, VMAT, and IMRT and found that HT showed superior dose conformity as compared with IMRT and VMAT in PTVs. As discussed by Zhang et al [28], the CI for PTV 59.4 was similar among the 4 techniques (TomoDirect, HT, VMAT, and fixed-field intensity-modulated radiotherapy), and the CI for PTV 50.4 showed a statistical significance of HT.…”
Section: Biomed Research Internationalmentioning
confidence: 52%
“…More importantly, the accurate prediction of RP is essential to facilitate individualized radiation dosing that leads to maximized therapeutic gain. At present, the risk assessment of RP is mainly predicted by using lung dosimetric parameters ( 5 , 6 ), such as the relative volume of total lung irradiated above a specified threshold dose (V X ) or mean lung dose (MLD): Although several metrics have appeared promising, the results vary across institutions, so these metrics do not seem to be perfect at predicting RP ( 7 , 8 ). In addition to dosimetric parameters, some clinical features (tumor stage, smoking history, preexisting lung diseases, concurrent chemotherapy, and radiation dose) are also considered to be related to RP occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies [17,18] suggest that TOMO is safe in the treatment of lung cancer. EC studies [19,20] compared lung dose parameters by selecting a few patients and designing several different physical plans; however, there is no real-world report on the occurrence of RP in EC after different irradiation techniques. We analysed the incidence of RP in 247 patients with EC undergoing RT.…”
Section: Discussionmentioning
confidence: 99%